PENGARUH KEMANDIRIAN DAERAH, SOLVABILITAS, LEVEL OF CAPITAL OUTLAY TERHADAP FINANCIAL DISTRESS PADA SAAT PANDEMI COVID-19 MELALUI JUMLAH PENDUDUK SEBAGAI PEMODERASI PADA PEMERINTAH KABUPATEN DAN KOTA DI PROVINSI PAPUA TAHUN 2019-2020 - Nurulita Aghisna Rahmatika; Moch Imron (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study is titled "The Influence of Regional Independence, Solvency, Level of Capital Outlay on Financial Distress During the Covid-19 Pandemic Through Population As Moderation in Regency and City Governments in Papua Province in 2019-2020". In this study, the number of residents as a moderation of the three variables. This research aims to test and analyze the influence of regional independence, solvency, and the level of capital outlay on financial distress in the Regency and City governments of Papua Province in 2019-2020. The research method used is quantitative. The population in this study was 29 regencies and cities in Papua Province in the Fiscal Year 2019-2020. The sampling technique used is the purposive sampling method. For data analysis methods using Moderated Regression Analysis (MRA). The results of this study showed that regional independence and the level of capital outlay had a significant effect on financial distress, while solvency had no significant effect on financial distress. The results of the moderation test showed that the number of residents affected regional independence and the level of capital outlay against financial distress while the number of residents did not affect solvency to financial distress.